Handgrip Dynamometry and Patient-Generated Subjective Global Assessment in Patients with Nonresectable Lung Cancer. (2nd January 2017) - Barata, Ana T.; Santos, Carla; Cravo, Marília; Vinhas, Maria do Céu; Morais, Catarina; Carolino, Elisabete; Mendes, Lino; Roldão Vieira, Jorge; Fonseca, Jorge
ABSTRACT: Introduction : Undernutrition is frequently associated with advanced lung cancer. Accurate nutritional assessment tools are important to provide the proper nutritional therapy. Handgrip dynamometry has already been used in these patients, and the findings suggest that it is a good indicator of nutritional status. Aims : The aim of this study was to evaluate the association between nutritional status and handgrip strength (HGS) in patients with nonresectable lung cancer. Methods : Cross-sectional study involving thirty-seven subjects with nonresectable lung cancer. Nutritional status was obtained using Patient Generated Subjective Global Assessment (PG-SGA), and muscle function was evaluated by HGS using a Jamar® handgrip dynamometer on the nondominant hand. The results of both methods were compared and correlated. Results : According to PG-SGA, 73% (n = 27) of the patients were moderately undernourished, and 8% (n = 3) were severely undernourished. In total, 81% (n = 30) were undernourished. HGS was below the 50th percentile in 57% of the patients (n = 21). We found a significant association between nutritional status according to PG-SGA and HGS ( P = 0.026, CI = 95%). Conclusions : Handgrip dynamometry can be a useful tool to evaluate the functional and nutritional status. It can be included in lung cancer patients evaluation, along with other nutritional assessment tools.